Nanotechnology-driven strategies for tilapia vaccines: Comparative evaluation of nanoemulsions and silica nanoparticles against Streptococcus agalactiae - Angela Mariana Lusiastuti; Siti Nurul Aisyiyah Jenie; Melati Septiyanti; Yulianti Sampora; Tanjung Penataseputro; Thavasimutu Citarasu; Desy Sugiani; Dewi Syahidah; Indah Dwiatmi Dewijanti; Hessy Novita; Tuti Sumiati; Uni Purwaningsih; et al. (Veterinary World)
Background and Aim: Streptococcosis, caused by Streptococcus agalactiae, is a significant disease in tilapia farming that results in substantial economic losses. While vaccination is the most effective method for prevention, current vaccines face challenges when administered orally or through immersion, primarily due to poor absorption and degradation in the fish’s digestive system. Nanotechnology offers new ways to improve vaccine delivery and effectiveness. This review compares two nanoparticle (NPs)-based systems – nanoemulsions and silica NPs (SiNP) – for delivering vaccines to tilapia. Nanoemulsions are small, stable droplets that protect the vaccine and help it stick to mucosal surfaces, making them more effective in triggering immune responses. SiNP are highly stable and can protect vaccines under harsh conditions but still face challenges in particle size and vaccine loading. The review highlights important factors, including particle size, stability, and surfactant composition, that affect the vaccine’s effectiveness. In practical terms, nanoemulsions are more suitable for use in Indonesia’s tropical aquaculture settings because they are easier to apply, more stable, and more effective in their current formulations. Further research is needed to improve both systems, especially to ensure long-term safety, improve delivery to mucosal tissues, and reduce production costs. Nanotechnology-based vaccines have a strong potential to improve fish health and reduce antibiotic use in aquaculture.